Multimode interference photonic switches - Al-Hetar, Abdulaziz M. (Spie-Soc Photoptical Instrumentation Engineers, 2008)
Photonic switches are becoming key components in advanced optical networks due to their various applications in optical communication. One of the key advantages of photonic switches is the fact that they redirect or convert light without any optical to electronic conversions and vice versa. As one type of optical switch, multimode interference (MMI) switches have received more attention in recent years due to their significant role. The structure and operation principle of various types of MMI switches are introduced, and the recent progresses of MMI switches are also discussed.